The Role Of Halal Awareness And Attitudes Towards Purchasing Intentions At Halal Bakeries - Baroya Mila Shanty; Fiandari, Yulist Rima (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
The intention to purchase halal food is influenced by both internal and external factors, including consumer awareness and attitudes toward halal products. This study examines the role of halal awareness and attitudes in shaping purchase intentions for halal bakery products. Despite the growing demand for halal-certified food, research specifically addressing consumer behavior in halal bakeries remains limited. Understanding the determinants of purchase intention in this segment is essential for strengthening the halal bakery industry and providing strategic insights for businesses.This study was conducted in Indonesia, involving 110 respondents who had purchased from a halal bakery at least once and were aged 17 years or older. The research employs a quantitative approach using Smart PLS 3.0 for data analysis. The findings reveal that halal awareness significantly influences both consumer attitudes and purchase intentions toward halal bakery products. Furthermore, attitude serves as a crucial mediator, reinforcing the relationship between halal awareness and purchasing behavior. These findings contribute to the growing body of research on halal consumption behavior, emphasizing the need for greater consumer education and branding strategies in the halal bakery sector. Businesses can leverage these insights to enhance consumer trust, improve marketing strategies, and optimize their product positioning in the competitive halal food market..